2017
DOI: 10.1103/physrevb.95.205119
|View full text |Cite
|
Sign up to set email alerts
|

Spectral hole lifetimes and spin population relaxation dynamics in neodymium-doped yttrium orthosilicate

Abstract: We present a detailed study of the lifetime of optical spectral holes due to population storage in Zeeman sublevels of Nd 3+ :Y 2 SiO 5 . The lifetime is measured as a function of magnetic field strength and orientation, temperature, and Nd 3+ doping concentration. At the lowest temperature of 3 K we find a general trend where the lifetime is short at low field strengths, then increases to a maximum lifetime at a few hundred mT, and then finally decays rapidly for high field strengths. This behavior can be mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 61 publications
1
52
1
Order By: Relevance
“…As seen the lifetimes generally increase at low fields, reach a maximum around 0.4 T, and then start to decrease for higher fields, similarly to the case of ions with I=0. In [20] it was found that a SLR model including the direct, Raman and Orbach processes explained well the high-field data for ions with I=0. In figure 4 the blue solid line shows the lifetime predicted by this model, using the fitted parameters [20] for this particular magnetic field angle (D 1 axis).…”
Section: Hyperfine Relaxation Modelmentioning
confidence: 68%
See 4 more Smart Citations
“…As seen the lifetimes generally increase at low fields, reach a maximum around 0.4 T, and then start to decrease for higher fields, similarly to the case of ions with I=0. In [20] it was found that a SLR model including the direct, Raman and Orbach processes explained well the high-field data for ions with I=0. In figure 4 the blue solid line shows the lifetime predicted by this model, using the fitted parameters [20] for this particular magnetic field angle (D 1 axis).…”
Section: Hyperfine Relaxation Modelmentioning
confidence: 68%
“…Finally, we comment on the lifetimes measured below 0.5 T, where spin flip-flops limit the spectral hole lifetime for ions with I=0 [20]. We first note that for fields down to about 0.15 T, the hyperfine Hamiltonian is still a perturbation to the Zeeman Hamiltonian, in which case one would expect the spin flip-flop process to mainly drive the R 0 transition shown in figure 3.…”
Section: Hyperfine Relaxation Modelmentioning
confidence: 91%
See 3 more Smart Citations